Bahasa Indonesia: Rancang Bangun Keuangan Syariah Era Digital: Pengembangan Teknologi Finansial Berbasis Ekonomi Syariah - Muhammad Abu Raafi; Muhamad Ramadhan Martadinata; Orina Beatrixa; Cahaya Gina; Siti Fadilah Awalyah Winata; Titania Mukti (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2025)
Purpose: This study examines the implementation of Sharia financial principles within the financial technology (fintech) ecosystem and diagnoses critical challenges in the digital transformation of Indonesia's Sharia financial sector. Design/methodology/approach: Using a qualitative literature-based approach, the research compiles data from academic sources (journals, books), industry reports, and relevant online publications on fintech and Sharia finance. Analysis employs descriptive-qualitative methods supplemented by content analysis. Findings: Sharia principles (prohibitions against riba, maysir, and gharar) have been integrated into Sharia fintech models based on contracts such as mudharabah and musyarakah. Sharia fintech demonstrably enhances financial inclusion, particularly for MSMEs. Primary constraints include low digital literacy, infrastructure disparities, and regulatory rigidity in responding to technological innovation. Contribution/Originality/Novelty: The study enriches academic discourse on the convergence of Sharia principles with digital financial innovation. Practically, it proposes policy- and education-based strategies for sustainable Sharia fintech development. The research novelty lies in its comprehensive identification of challenges and formulation of strategic frameworks for Sharia fintech advancement in the digital era.